Strategi Implementasi Proyek Penguatan Profil Pelajar Pancasila di MTS Almarif 01 SingosariMalang - Ira Wirdatus Solichah; Samsul Susilawati (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The purpose of this study is to describe (1) the concept of pelajar pancasila, (2) the implementation strategy of the penguatan profil pelajar pancasila, (3) the challenges and efforts to improve the implementation of the penguatan profil pelajar pancasila’s project. (4) preparation of penguatan profil pelajar pancasila’s project in MTS Almaarif 01 Singosari the method used is descriptive qualitative method. The source of data from this study is the head of the Madrasah, teachers, and learners. Researchers collected data by observation and interview. The result is (1) profil pelajar pancasila has a long-term goal in the learning process that takes place in schools. (2) Implementation Penguatan Profil Pelajar Pancasila’s project can be done through intracurricular, co-curricular, and extracurricular activities. (3) Challenges in the implementation of the Penguatan profil pelajar pancasila include low awareness and understanding of Pancasila values among students and the community, there are values that are contrary to Pancasila or there are influences that are not in line with these values. From the educator factor, the obstacles include limited time of teaching and learning activities, minimal lesson substance, and very less student interest in the subject. (4) preparations made by MTS Almaarif 01 Singosaru are socialization, technical guidance on training on making teaching modules and project modules. Project planning activities consist of the first; designing the allocation of time and dimensions of the pancasila student profile. Second, form a project facilitation team. Third, identify the level of readiness of the madrasah. Fourth, the selection of general themes.Fifth, the determination of specific themes.